Robot-assisted off-clamp enucleation of endophytic tumor in solitary functioning kidney - Riccardo Bertolo; Filippo Migliorini; Alessandro Veccia; Luca Roggero; Greta Pettenuzzo; Francesco Ditonno; Francesco Artoni; Claudio Brancelli; Alessandro Antonelli (Urology Video Journal)
Objective: To report a case of an off-clamp robot-assisted enucleation of endophytic renal mass performed in a patient with a solitary functioning kidney. Patient and surgical procedure: The patient underwent a contrast-enhanced CT scan following a syncopal episode, which showed a right renal mass of 3 cm at the hilum with a RENAL score of 9. Hypoperfusion of the contralateral kidney was observed due to renal artery stenosis. A radionuclide renal scan confirmed the poor contribution of the left kidney to renal function. The patient was counseled for robot-assisted partial nephrectomy. The arterial vascular pedicle was dissected at the extra-parenchymal level, guided by 3D reconstruction. After identifying the tributary branch of the area of interest, a branch of the renal artery was suspended on a vascular loop with the help of ischemia simulation on the 3D model. Tumor resection was initiated without clamping the renal artery, identifying the plane of the tumor pseudocapsule. Dissection was conducted circumferentially around the lesion to reduce tractions and the likelihood of tumor rupture. After liberating the lateral margins of the lesion, the enucleation of the more endophytic portion was completed. A hybrid cortico-medullary suture was performed using the ''sliding clips'' technique. Results: The surgery was uneventful. Console time was 65 min. Blood loss was 300 ml. The final pathology showed a papillary renal cell carcinoma, grade 2, with negative margins. Functional follow-up showed no immediate impact of the intervention, and at a three-month follow-up, there were no variations in serum creatinine levels and glomerular filtration rate. Conclusions: Our approach combined an off-clamp technique with anatomical resection and minimal renorrhaphy. Given the case's complexity, the arterial pedicle was selectively prepared according to the 3D model to be ready for selective clamping on demand. Our experience emphasizes the importance of advanced imaging and simulation in complex surgical planning and execution.